Diagnostic accuracy of fecal calprotectin in assessing the severity of inflammatory bowel disease: From laboratory to clinic - Soheila Moein; Durdi Qujeq; Mostafa Vaghari Tabari; Mehrdad Kashifard; Karimollah Hajian (Babol University of Medical Sciences, 2017)
Background: Inflammatory bowel disease (IBD) involves chronic inflammation of the digestive tract. In the past decades, fecal calprotectin has been proposed as a useful biomarker for the differential diagnosis between IBD patients and healthy controls. We designed this study to evaluate the diagnostic ability of fecal calprotectin (FC) and conventional inflammatory markers in IBD patients. Methods: Thirty patients who underwent colonoscopy were cases and thirty healthy subjects undergoing colonoscopy as part of a medical check-up were the controls. These 2 groups were evaluated with regard to age and sex. Severity of the disease was evaluated based on disease endoscopic index. FC, Cross reactive protein (CRP) and Erythrocyte sedimentation rate (ESR) were measured using ELISA, colorimetric and Westergren methods, respectively. The obtained data were analyzed by independent test, correlation test and receiver operating characteristic (ROC) curve analysis. A p<0.05 was considered statistically significant. Results: Fecal calprotectin level in the case group increased compared to control group (p<0.05).  Moreover FC has stronger correlation with disease endoscopic activity than conventional inflammatory markers (r=0.847 versus r= -0.44 for CRP and r=0.054 for ESR in Crohn's disease and r=0.798 versus r=0.463 for CRP and r=0.467 for ESR in ulcerative colitis). Receiver operating characteristic (ROC) curve analysis showed FC has larger area under the curve (AUC) than conventional inflammatory markers (1 versus 0.849 for CRP and 0.846 for ESR). Conclusion: Discriminating IBD patients from healthy controls was better for FC than conventional inflammatory markers. Additionally, the results produced by FC correlate with the severity of IBD.